At the limits of digital education. The importance of practical education for clinical competencies learning in the field of emergency medicine: A controlled non-randomized interventional study - Vogt, Lina; Schauwinhold, Michael; Rossaint, Rolf; Schenkat, Henning; Klasen, Martin; Sopka, Saša (Frontiers in Medicine, 2022)
Introduction: A high-quality education of future physicians is essential. Modern approaches interlock the acquisition of theoretical knowledge and practical skills in a spiral curriculum, leading to a mutual learning benefit for knowledge and application. This model was challenged by the elimination of hands-on trainings during the pandemic, which were often replaced by purely digital teaching models. Given the holistic nature of the spiral curriculum, we assumed that a purely digital model would have an impact on knowledge acquisition due to missing hands-on learning opportunities. The aim of the study was to investigate, using an emergency seminar as an example, whether purely digital training leads to a difference in theoretical knowledge compared to the traditional model. Materials and methods: Study design: We used a two-groups design comparing a sample of medical students taught in 2020 with a purely digital teaching format (DF) with a historical control group taught with a traditional format (TF). Subject of investigation was a seminar on emergency medicine, taking place in the 4th year. Outcome parameters The primary outcome parameter was the students' acquired knowledge, measured by the score achieved in the final exams. Students’ evaluation of the seminar was used as a secondary outcome parameter. Results: Students in the DF group scored significantly lower than students in the TF group in the final exams. Students in the DF group rated the course significantly worse than students in the TF group. Discussion: The study results illustrate that purely digital education leads to inferior knowledge acquisition compared to the traditional spiral curriculum. A possible explanation may lie in a deeper processing of the information (e.g., understanding the information by experience and analysis) and accordingly a better memory recall. Moreover, the students' critical appraisal of the DF may have had an unfavorable effect on learning performance. Moderating factors may be lower learning motivation or the "zoom fatigue" effect. Conclusion: These study results clearly illustrate the importance of hands-on teaching for knowledge acquisition. The interlocking of theoretical knowledge and practical skills, as ensured by the spiral curriculum, is essential.